Chromobacterium violaceum (Schröter 1872) isolated from the aquatic environment associated with the fish culture of Jaú, Zungaro jahu (Ihering, 1898) (Siluriformes, Pimelodidae) (Bioscience Journal, 2017)
The jau, Zungaro jahu (Ihering, 1898) is an endangered species, rheophilic, reaching 1.5 m and more than 100 kg. During a work of microbiological monitoring of water quality, in the cultivation of Zungaro jahu, microorganisms that were isolated, were previously reported in other studies, as family members Enterobacteriaceae, Staphylococcus and non-fermenting bacilli. However, it was also isolated Chromobacterium violaceum, which despite being a bacterium found in such an environment, it was reported linked to the cultivation of fish. This paper describes the Chromobacterium violaceum founded in a psiculture, which has implications for national fish farming.